The Immunoevasive Function Encoded by the Mouse Cytomegalovirus Gene m152 Protects the Virus against T Cell Control in Vivo - Krmpotic, Astrid (The Rockefeller University Press, 1999)
Cytomegaloviruses encode numerous functions that inhibit antigen presentation in the major histocompatibility complex (MHC) class I pathway in vitro. One example is the mouse cytomegalovirus (MCMV) glycoprotein gp40, encoded by the m152 gene, which selectively retains murine but not human MHC class I complexes in the endoplasmic reticulum–Golgi intermediate compartment/cis-Golgi compartment (Ziegler, H., R. Thäle, P. Lucin, W. Muranyi, T. Flohr, H. Hengel, H. Farrell, W. Rawlinson, and U.H. Koszinowski. 1997. Immunity. 6:57–66). To investigate the in vivo significance of this gene function during MCMV infection of the natural host, we constructed recombinants of MCMV in which the m152 gene was deleted, as were the corresponding virus revertants. We report on the following findings: Deletion of the m152 gene has no effect on virus replication in cell culture, whereas after infection of mice, the m152-deficient virus replicates to significantly lower virus titers. This attenuating effect is lifted by reinsertion of the gene into the mutant. Mutants and revertants grow to the same titer in animals deprived of the function targeted by the viral gene function, namely in mice deficient in β2-microglobulin, mice deficient in the CD8 molecule, and mice depleted of T cells. Upon adoptive transfer of naive lymphocytes into infected mice, the absence of the m152 gene function sensitizes the virus to primary lymphocyte control. These results prove that MHC-reactive functions protect CMVs against attack by CD8(+) T lymphocytes in vivo.